Laicismo, catolicismo y nacionalismo en la musicología española (1914-1953) - Pilar Ramos López (Resonancias, 2013)
Studies on Spanish musical historiography have been centred on its nationalism, overlooking political and religious nuances. This paper aims to differentiate within nationalism a ‘lay’ or secular historiographical tradition, and an ecclesiastical one, whose main scholars are, respectively, Rafael Mitjana and José Subirá on the one hand, and Higinio Anglés y Suñol, on the other. The differences between both traditions become evident in the musicological texts as well as in the positions of power held by ecclesiastical researchers through the period under study, during which the Instituto Español de Musicología was created.